Crescimento relativo do camarão canela Macrobrachium amazonicum (Heller) (Crustacea, Decapoda, Palaemonidae) em viveiros - Moraes-Riodades, Patrícia M.C. [UNESP]; Valenti, Wagner Cotroni [UNESP] (Sociedade Brasileira de Zoologia, 2002)
Some morphometric relationships in Macrobrachium amazonicum (Heller, 1862) reared in earthen ponds were studied. A total of 239 individuals were collected, sexed and sorted to juvenile or adult. Total length (Lt), post-orbital length (Lpo), carapace length (Lcp) and queliped length (Lql) were measured. The relationships Lt/Lpo, Lpo/Lcp and Lt/Lcp are the same for juveniles, males and females, indicating unchanged growth pattern during post-larval ontogenetic development. While Lt/Lpo showed isometric growth, Lpo/Lcp and Lt/Lcp showed negative allometry. on the other hand, for the Lql/Lcp relationship, juveniles showed isometric growth, females slight positive allometry and males a strong positive allometry. It suggests that the importance of chelipeds may be different in these groups. Quelipeds play important role on food capture and on agonistic, social and reproductive behavior. Therefore, inter and intraspecific interactions may change during prawn growth, even after morphological
Relative growth of Amazon river prawn Macrobrachium amazonicum (Heller) (Crustacea, Decapoda, Palaemonidae) in earthen ponds
Keywords: Crustacea; Macrobrachium amazonicum; freshwater prawn; relative growth; Amazon river prawn